Energy storage carbon material and preparation method and application thereof
The preparation of energy storage carbon materials through one-step carbonization of biomass waste has solved the problem of heavy metal ions in industrial wastewater, and provided high-performance negative electrode materials for secondary batteries, achieving low-cost and efficient battery material preparation.
Patent Information
- Application Number
- CN202411578480.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the prior art, when treating heavy metal ions in industrial wastewater, there are problems such as high energy consumption, high cost, long treatment cycle and secondary pollution, and the low capacity of the negative electrode material of the secondary battery and slow ion transmission.
By carbonizing the biomass waste enriched with metal ions in one step, it is converted into energy storage carbon materials, and using the biomass' own elements such as sulfur, phosphorus, nitrogen, etc. to react with metal ions, it is converted into metal sulfur, phosphorus, and nitrogen in situ in situ. Chemicals, used in secondary battery energy storage materials.
It realizes low-cost and high-performance battery material preparation, simplifies the process flow, avoids secondary pollution of high-risk chemicals, and improves the specific capacity and fast charging performance of the battery.
Smart Images

Figure CN119430134A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater purification and energy storage materials, and in particular to an energy storage carbon material and a preparation method and application thereof. Background Art
[0002] Chemical, mining, pharmaceutical, printing and dyeing, papermaking and other industries will produce a large amount of industrial wastewater containing heavy metal ions (such as mercury, chromium, copper, cadmium, lead, etc.). If these wastewaters are not effectively controlled and reasonably treated and are discharged at will, they will cause serious environmental pollution and waste of resources. At present, adsorption is a more commonly used method to solve such industrial wastewater containing heavy metal ions. Agricultural and forestry wastes (such as straw, rice husks, peanut shells, grapefruit peels, wood, bamboo, shells, lobsters, etc.) contain active groups (including hydroxyl, carboxyl and amino groups) that can be used as adsorption sites for heavy metals. However, no matter what kind of biomass material is used as the raw material of the heavy metal adsorbent, after the adsorption of heavy metals, harmful solid waste adsorbents will still be produced. Therefore, the post-treatment or further utilization of these hazardous solid waste adsorbents is still a key issue in the current field of adsorption materials.
[0003] At present, the post-treatment methods for enriched heavy metal plant adsorbents include incineration, composting, etc. Incineration is a combustion reaction through excess air, which may cause secondary pollution of metal-containing fly ash, and its energy consumption is high, increasing operating costs; composting is a technology that uses microorganisms to degrade pollutants in solid waste, but its treatment cycle is long (usually two to three months), the cost of large-scale treatment is high, and the leachate generated during the composting process needs to be strictly controlled.
[0004] Faced with the new energy situation and climate change, the development direction of science and technology has gradually shifted to the development and utilization of green, renewable clean energy. Energy storage technology can convert clean energy such as wind energy and solar energy that are difficult to store into a more convenient and economical form. Secondary batteries are the most important part of energy storage technology. They have the advantages of being easy to use, less environmental pollution, and not restricted by geographical location. However, in order to achieve large-scale application, their energy density and production cost still need to be further optimized. Biomass has broad application prospects in the fields of energy and environment. Biomass carbon not only has a large specific surface area, rich and adjustable pore structure, good conductivity, and stable electrochemical properties, but can also increase the conductivity and additional active sites of carbonaceous materials through self-doping effects (for example, nitrogen, sulfur, phosphorus and other elements). In particular, biomass-derived carbon loaded with corresponding metal nitrogen (sulfur, phosphorus) compounds can be used as an excellent secondary battery negative electrode material. At the same time, the unique natural advantages of biomass raw materials, abundant sources, environmental friendliness, and easy processing and structural design make biomass carbon materials an ideal candidate material for secondary batteries.
[0005] CN115571879A cultivates biomass in soil or sewage environment contaminated by metal ions, and then the biomass obtained by growing for a certain period of time is dried, pre-oxidized, activated, carbonized, etc., and a series of post-treatments are obtained to obtain an active material with energy storage structure and electrochemical performance. However, the method has limited absorption of pollutants, lacks an assessment of purification ability, and the enrichment cycle of metal elements is quite long (cultivation cycle is 7 days-90 days). In the process of converting biomass into energy storage carbon material, porous carbon is prepared using traditional pore-forming agents, which is cumbersome to operate, and the process in which heavy metal elements are converted into metal nitrides depends on external nitrogen sources, which increases the preparation cost, and the metal compound species displayed are single, lacking adaptability in different directions in the field of energy storage.
[0006] CN104084221A uses biosorption technology to enrich heavy metal ions in industrial wastewater onto biomass powder particles, and then mixes the biomass powder loaded with heavy metal ions with S-containing 2- 、Se 2- The method involves a contact reaction with a reagent (sodium sulfide, sodium hydrosulfide, thiourea, hydrogen sulfide or sodium selenide, sodium hydroselenide, selenourea, hydrogen selenide, etc.) to convert the heavy metal ions adsorbed on the biomass powder particles into corresponding metal sulfides (selenides) in situ for use in the field of photocatalysis. Similarly, this method requires a large amount of highly polluting and highly toxic chemical reagents to assist in the preparation process, and requires additional alkaline washing treatment for the biomass, which increases the complexity and danger of the process flow, and lacks experimental verification of the heavy metal adsorption capacity of the relevant biomass.
[0007] Therefore, exploring a low-cost, simple process, and easy-to-scale method to achieve controllable preparation of energy storage carbon materials remains a major challenge in the field of energy storage material preparation. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems existing in the prior art and to provide an energy storage carbon material and a preparation method and application thereof.
[0009] Based on the concept of treating waste with waste, the present invention utilizes biomass waste to achieve the adsorption of metal ions, and also carbonizes the hazardous solid waste adsorbent in the adsorption process in one step, so that the metal ions adsorbed on the biomass particles react with the sulfur (phosphorus, nitrogen) functional groups of the biomass itself, and are converted in situ into corresponding metal sulfides (phosphorus, nitrogen) compounds, which can be used as secondary battery energy storage materials. Different from other metal compound composite materials, which use a large amount of chemical reagents in the preparation process, have complex processes, cumbersome processes, and are easy to pollute the environment, the present invention is expected to be widely used in the preparation of low-cost, high-performance battery materials.
[0010] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing an energy storage carbon material, wherein the method comprises: carbonizing biomass waste enriched with metal ions to obtain the energy storage carbon material.
[0011] The method of the present invention can transform various valuable heavy metal ions in industrial wastewater from a waste state into a high-quality raw material source for producing secondary battery energy storage materials.
[0012] The second aspect of the present invention provides an energy storage carbon material prepared according to the method described in the first aspect.
[0013] The third aspect of the present invention provides the use of the energy storage carbon material according to the second aspect in the preparation of a secondary metal / ion battery.
[0014] A fourth aspect of the present invention provides a secondary metal / ion battery, wherein the battery uses the energy storage carbon material described in the second aspect as a negative electrode material.
[0015] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0016] (1) The present invention converts biomass waste enriched with metal ions into energy storage carbon materials with outstanding metal affinity through a one-step carbonization process, making full use of the sulfur, phosphorus, nitrogen and other elements of the biomass itself, and can achieve the successful preparation of metal compounds without the assistance of additional chemical reagents, greatly simplifying the process flow and avoiding the secondary pollution problem of high-risk chemicals.
[0017] (2) The energy storage carbon material prepared by the present invention can promote the uniform deposition of metals during the charging and discharging process and avoid safety problems caused by dendrite growth. At the same time, the metal ions in industrial wastewater can be used to prepare and produce high value-added secondary battery energy storage materials by means of a simple and low-cost method of biosorption.
[0018] (3) The present invention can flexibly control the type of metal compound generated by adjusting the carbonization temperature. As the carbonization temperature increases, the adsorbed metal ions will be converted into metal nitrides, metal sulfides, and metal phosphides in turn. At higher temperatures, the metal compounds will be reduced and volatilized, and the remaining parts will be doped into the carbon in the form of single atoms or nanoclusters. The holes left by the volatilization make the material form a porous carbon structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the adsorption kinetics test result of rapeseed meal waste on cadmium ions in Example 1 of the present invention.
[0020] Figure 2 This is the adsorption isothermal test result of rapeseed meal waste on cadmium ions in Example 1 of the present invention.
[0021] Figure 3 It is a transmission electron microscope image of the energy storage carbon material prepared in Example 1 of the present invention.
[0022] Figure 4 This is the XRD diagram of the energy storage carbon material prepared in Example 1 of the present invention.
[0023] Figure 5 This is a Raman spectrum of the energy storage carbon material prepared in Example 1 of the present invention.
[0024] Figure 6 This is the overall X-ray photoelectron spectrum of the energy storage carbon material prepared in Example 1 of the present invention.
[0025] Figure 7 This is a high-resolution spectrum of the S element of the energy storage carbon material prepared in Example 1 of the present invention.
[0026] Figure 8 This is a high-resolution spectrum of the Cd element of the energy storage carbon material prepared in Example 1 of the present invention.
[0027] Fig. 9 This is a coulombic efficiency test chart of the energy storage carbon material prepared in Example 1 of the present invention as a sodium metal negative electrode modification material in a button-type half-cell.
[0028] Fig.10 This is a test chart of the cycle stability of the energy storage carbon material prepared in Example 1 of the present invention as a sodium metal battery modification material in a symmetrical battery.
[0029] Fig.11 This is a rate performance test diagram of the energy storage carbon material prepared in Example 1 of the present invention when used as a sodium metal battery modification material in a full battery.
[0030] Fig.12 This is a long cycle performance test chart of the energy storage carbon material prepared in Example 1 of the present invention as a sodium metal battery modification material in a full battery.
[0031] Fig.13 It is a transmission electron microscope image of the energy storage carbon material prepared in Example 10 of the present invention. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] A first aspect of the present invention provides a method for preparing an energy storage carbon material, wherein the method comprises: carbonizing biomass waste enriched with metal ions to obtain the energy storage carbon material.
[0034] The key technical problem to be solved by the present invention is to change the current situation of secondary pollution caused by post-treatment of highly toxic heavy metal ion adsorbents (with agricultural and forestry waste as raw materials) in traditional industrial wastewater treatment, while overcoming the problems of low capacity, slow ion transmission, uneven metal deposition, dendrite growth, volume expansion, etc. of existing secondary battery negative electrode materials. The present invention combines the removal of valuable metal ions in wastewater with the preparation and production of high value-added energy storage materials, fully utilizes the active functional groups of biomass itself and the miscellaneous elements such as sulfur, phosphorus, and nitrogen therein, and converts highly toxic heavy metal ions in situ into metal compound nanoparticles uniformly dispersed in biomass carbon.
[0035] During the charge and discharge process of secondary metal / ion batteries, the introduction of metal compound nanoparticles can not only provide additional nucleation sites, but also effectively reduce the diffusion energy barrier of ions on the electrode surface, accelerate ion transport and desolvation processes, and greatly improve the battery's specific capacity and fast charging performance. This is of great significance for the preparation of low-cost, high-performance secondary battery negative electrode materials and thus promoting the large-scale application of secondary batteries.
[0036] In some embodiments of the present invention, the metal ion is selected from at least one of magnesium ion, calcium ion, chromium ion, manganese ion, iron ion, cobalt ion, nickel ion, copper ion, zinc ion, lead ion and cadmium ion.
[0037] In some embodiments of the present invention, the carbonization is performed under a protective atmosphere.
[0038] In some embodiments of the present invention, the protective atmosphere is an argon or nitrogen atmosphere.
[0039] In some embodiments of the present invention, the carbonization process includes: heating to 100-300°C (carbonization temperature) at a heating rate of 1-20°C / min and keeping warm for 0.5-2h, then heating to 400-2000°C at the same heating rate and keeping warm for 1-3h.
[0040] In some embodiments of the present invention, the carbonization process includes: heating to 150°C at a heating rate of 2.5°C / min and keeping warm for 30 minutes; then heating to 600°C (carbonization temperature) at the same heating rate and keeping warm for 1 hour.
[0041] The present invention can realize controllable regulation of the types of generated metal compounds by adjusting the carbonization temperature to meet the requirements for the performance of energy storage carbon materials in different application scenarios.
[0042] For example, metal oxides have the advantages of high specific capacitance, high conductivity, high natural abundance, rich valence states, and easy design and manufacturing, etc. Therefore, they are widely used as supercapacitor electrode materials, but their disadvantages are mainly manifested in short cycle life and large gap between actual capacitance and theoretical capacitance.
[0043] Metal sulfides have been widely studied due to their advantages such as good conductivity, low cost, low electronegativity, good semiconductor properties, and good redox activity. Since the electronegativity of sulfur atoms is weaker than that of oxygen atoms, metal sulfides have higher conductivity, thermal stability, mechanical stability, and electrochemical properties than the corresponding metal oxides under the same conditions. However, during frequent charging and discharging, it is very easy to aggregate, resulting in reduced capacity. In addition, fluctuations, expansion, thermodynamic instability, acid oxidation, and volatility of metal sulfides are common problems in actual market applications.
[0044] Metal phosphides have metal-like properties, abundant redox reaction sites and excellent electrical conductivity. Due to the large radius of the phosphorus atom, phosphides present a variety of crystal structures. In addition, the low electronegativity of phosphorus ensures fast charge transfer. Compared with metal oxides, metal phosphides are conducive to fast electron transport in high power density energy storage devices. However, there are often multiple phase components in their preparation process, so the synthesis of pure transition metal phosphides is still challenging.
[0045] The present invention can achieve controllable regulation of the types of metal compounds through a simple preparation method, providing ideas for the preparation of high-performance electrode materials in the future.
[0046] In some embodiments of the present invention, the energy storage carbon material is a carbon material loaded with metal compound nanoparticles.
[0047] In some embodiments of the present invention, the metal compound is selected from at least one of magnesium oxide, magnesium sulfide, chromium oxide, chromium sulfide, manganese oxide, manganese sulfide, iron oxide, iron phosphide, iron sulfide, cobalt oxide, cobalt phosphide, cobalt sulfide, nickel oxide, nickel sulfide, nickel phosphide, nickel nitride, copper oxide, copper sulfide, copper phosphide, zinc oxide, zinc sulfide, zinc phosphide, cadmium oxide, cadmium sulfide, cadmium phosphide and metal compounds of the same family.
[0048] In some embodiments of the present invention, the biomass waste enriched with metal ions is obtained by the following method: the biomass waste is crushed, washed and dried, added to wastewater containing metal ions for adsorption, and after the adsorption is completed, the biomass waste enriched with metal ions is obtained by centrifugal filtration.
[0049] In the present invention, the wastewater containing metal ions can be either simulated wastewater containing metal ions prepared in a laboratory or actual industrial wastewater containing metal ions sampled from a relevant industrial site.
[0050] The present invention selects natural biomass waste as metal ion adsorbent, does not require additional chemical treatment of the biomass, utilizes the abundant active groups of the plant itself as adsorption sites, and the capillary action of the plant itself and the concentration difference effect of the system enable the metal ions to be uniformly adsorbed in the biomass, with a short cycle, low cost and simple process.
[0051] In the present invention, magnetic stirring or a temperature-controlled shaking table is used during the adsorption process. After the adsorption is completed, centrifugal filtration is performed, and the biomass waste is collected and dried in a forced air drying oven for 24 hours.
[0052] In some embodiments of the present invention, the biomass waste contains S-glycoside, -SH, -NH2, PO, -OH or -COOH active functional groups.
[0053] In some embodiments of the present invention, the biomass waste is selected from at least one of rapeseed meal, bagasse and soybean meal.
[0054] In some embodiments of the present invention, the pH value of the metal ion-containing wastewater is 2-12, preferably 5-7.
[0055] In some embodiments of the present invention, the amount of biomass waste added is 0.1-100 g / L, preferably 1-20 g / L.
[0056] In some embodiments of the present invention, the adsorption time is 10-2000 min, preferably 500-1500 min.
[0057] The second aspect of the present invention provides an energy storage carbon material prepared according to the method described in the first aspect.
[0058] The third aspect of the present invention provides the use of the energy storage carbon material according to the second aspect in the preparation of a secondary metal / ion battery.
[0059] A fourth aspect of the present invention provides a secondary metal / ion battery, wherein the battery uses the energy storage carbon material described in the second aspect as a negative electrode material.
[0060] The present invention uses biological waste to efficiently purify industrial wastewater while preparing energy storage carbon materials loaded with metal compounds through one-step carbonization, and no additional chemical reagents are required throughout the process, which maximizes the greenness and environmental protection of the preparation process. By adjusting the carbonization temperature, the types of metal compounds can also be controlled. The present invention combines the utilization of biomass resources, the purification of heavy metal pollutants, and the recycling of waste adsorbents. Further application of the present invention to secondary batteries such as lithium and sodium can induce uniform nucleation of metal ions on their surfaces, promote the smooth deposition of metals, and exhibit high energy density and excellent cycle performance.
[0061] The present invention will be described in detail below through examples.
[0062] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0063] Example 1
[0064] This example is used to illustrate a method for preparing an energy storage carbon material using rapeseed meal as a raw material.
[0065] Add 50 mL of 0.2 g / L Cd into the centrifuge tube. 2+ The solution was added with 0.1 g of rapeseed meal, placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation and adsorption for 600 min, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature was cooled to room temperature, an energy storage carbon material loaded with cadmium sulfide nanoparticles was obtained.
[0066] Figure 3-Figure 8 The prepared energy storage carbon materials were characterized.
[0067] Example 2
[0068] This example is used to illustrate a method for preparing energy storage carbon material using bagasse as raw material.
[0069] Add 50 mL of 0.2 g / L Cd into the centrifuge tube. 2+ The solution was added with 0.1 g of bagasse, placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation adsorption for 600 min, the bagasse was filtered and collected, and placed in a blast drying oven for thorough drying. The dried bagasse was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature is cooled to room temperature, the energy storage carbon material is obtained.
[0070] Example 3
[0071] This example is used to illustrate a method for preparing energy storage carbon material using soybean meal as raw material.
[0072] Add 50 mL of 0.2 g / L Cd into the centrifuge tube. 2+The solution was added with 0.1 g of soybean meal, placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation and adsorption for 600 min, the soybean meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried soybean meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature is cooled to room temperature, the energy storage carbon material is obtained.
[0073] Example 4
[0074] This example is used to illustrate the method for preparing energy storage carbon material.
[0075] Add 50 mL of 0.2 g / L Zn 2+ The solution was added with 0.1 g of rapeseed meal, which was placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation and adsorption for 600 min, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature was cooled to room temperature, the energy storage carbon material was obtained.
[0076] Example 5
[0077] This example is used to illustrate the method for preparing energy storage carbon material.
[0078] Add 50 mL of 0.2 g / L Ni into the centrifuge tube. 2+ The solution was added with 0.1 g of rapeseed meal, which was placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation and adsorption for 600 min, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature was cooled to room temperature, the energy storage carbon material was obtained.
[0079] Example 6
[0080] This example is used to illustrate the method for preparing energy storage carbon material.
[0081] The wastewater discharged from a cadmium electroplating workshop was obtained, and the cadmium ion content was measured to be 0.11 g / L. After adjusting the pH value of the solution to 7.0, 50 mL of the above solution was added to a centrifuge tube, and 0.1 g of rapeseed meal was added, which was placed in a constant temperature shaker (25°C, 150 r / min). After 600 minutes of shaking adsorption, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried sample was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere, and then kept warm for 30 minutes; then heated to 600°C at the same heating rate and kept warm for 1 hour. When the temperature is cooled to room temperature, the energy storage carbon material is obtained.
[0082] Example 7
[0083] This example is used to illustrate the method for preparing energy storage carbon material.
[0084] Add 50 mL of 0.2 g / L Cd into the centrifuge tube. 2+ The solution was added with 0.1 g of rapeseed meal, stirred and reacted for 600 min, the rapeseed meal was collected by filtration, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 1 h. When the temperature was cooled to room temperature, the energy storage carbon material was obtained.
[0085] Example 8
[0086] This example is used to illustrate the method for preparing energy storage carbon material.
[0087] Add 50 mL of 0.2 g / L Ni into the centrifuge tube. 2+ The solution was added with 0.1 g of rapeseed meal, which was placed in a constant temperature shaker (25°C, 150 r / min). After oscillation and adsorption for 600 min, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace. Under an argon atmosphere, the temperature was increased to 100°C at a heating rate of 5°C / min and then kept warm for 30 min; then the temperature was increased to 700°C at the same heating rate and kept warm for 1 h. When the temperature was cooled to room temperature, an energy storage carbon material loaded with nickel sulfide nanoparticles was obtained.
[0088] Example 9
[0089] This example is used to illustrate the method for preparing energy storage carbon material.
[0090] Add 50 mL of 0.2 g / L Cd into the centrifuge tube. 2+The solution was added with 0.1 g of rapeseed meal, which was placed in a constant temperature shaker (25°C, 150 r / min), and after oscillation and adsorption for 600 min, the rapeseed meal was filtered and collected, and placed in a blast drying oven for thorough drying. The dried rapeseed meal was taken out and transferred to a tubular furnace, and heated to 100°C at a heating rate of 5°C / min in an argon atmosphere and then kept warm for 30 min; then heated to 600°C at the same heating rate and kept warm for 3 h. When the temperature was cooled to room temperature, the energy storage carbon material was obtained.
[0091] Example 10
[0092] The energy storage carbon material was prepared according to the method of Example 1, except that the carbonization temperature was adjusted from 600°C to 900°C to obtain a porous carbon energy storage carbon material doped with a single cadmium atom. Fig.13 shown.
[0093] When the carbonization temperature reaches 900°C, cadmium sulfide undergoes an oxidation-reduction reaction with the carbon matrix, converting into cadmium element which then volatilizes due to heat, leaving a porous structure in the carbon matrix. Part of the cadmium element is doped into the carbon in the form of single atoms, providing reaction activity for subsequent electrochemical processes.
[0094] Embodiment 11
[0095] An energy storage carbon material was prepared according to the method of Example 8, except that the carbonization temperature of 700° C. was adjusted to 500° C. to obtain an energy storage carbon material loaded with nickel oxide nanoparticles.
[0096] Example 12
[0097] An energy storage carbon material was prepared according to the method of Example 8, except that the carbonization temperature was adjusted from 700° C. to 1000° C. to obtain an energy storage carbon material loaded with nickel phosphide nanoparticles.
[0098] Comparative Example 1
[0099] Add 50 mL of deionized water and 0.1 g of rapeseed meal to a centrifuge tube, place it in a constant temperature shaker (25°C, 150 r / min), shake for 600 min, filter and collect the rapeseed meal, put it into a blast drying oven for thorough drying, take out the dried rapeseed meal and transfer it to a tubular furnace, heat it to 100°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 30 min; then heat it to 600°C at the same heating rate and keep it warm for 1 h. When the temperature is cooled to room temperature, the plant carbon material is obtained.
[0100] Test Example 1
[0101] (1) Add 50 mL of a series of Cd concentrations into a centrifuge tube. 2+The solution was added with 0.1 g of rapeseed meal material, placed in a constant temperature shaker (25°C, 150 r / min), and after shaking and adsorption for the corresponding time, the supernatant was centrifuged and the residual amount of heavy metal ions after adsorption was determined by ICP-MS. The results of adsorption kinetics and adsorption isotherm experiments are shown in Figure 1 and Figure 2 shown.
[0102] (2) The adsorption capacity of different biomass wastes in Examples 1-3 was verified, and the results are shown in Table 1 and Table 2.
[0103] Table 1 Effect of different biomass waste on Cd 2+ The adsorption kinetics experimental results
[0104]
[0105]
[0106] Table 2 Effect of different biomass waste on Cd 2+ Adsorption isotherm experimental results
[0107]
[0108] From the results of the adsorption amount changing with adsorption time in Table 1, the three biomass wastes have a significant influence on the adsorption of Cd 2+ The adsorption rate was very fast, and the adsorption equilibrium was basically reached within 240 min. The adsorption amount was above 18 mg / g, and the adsorption capacity was considerable. The isothermal adsorption experimental results in Table 2 show that the adsorption amount of different biomasses increased with the increase of metal ion concentration in the solution, and finally reached the adsorption equilibrium.
[0109] (3) The adsorption capacity of rapeseed meal waste in Examples 4-6 for different types of metal ion solutions was evaluated.
[0110] Table 3 Adsorption capacity of rapeseed meal waste on different types of metal ion solutions
[0111]
[0112] As can be seen from Table 3, rapeseed meal has a significant effect on Zn 2+ 、Ni 2+ 、Cd 2+ The adsorption amount increases rapidly with time, that is, the adsorption rate is fast, followed by a slower adsorption process, and finally reaches adsorption equilibrium (about 240min). In addition, the adsorption capacity of rapeseed meal for different metal ions remains above 18mg / g, which proves that the method of using biomass waste to adsorb metal ions in solution to provide a metal source for subsequent carbonization has a certain universality.
[0113] Test Example 2
[0114] The energy storage carbon materials prepared in Examples 1-9 and the plant carbon materials prepared in Comparative Example 1 were mixed with a conductive agent and a binder at a mass ratio of 8:1:1, wherein the conductive agent was acetylene black and the binder was PVDF (polyvinylidene fluoride). NMP (N-methylpyrrolidone) was used as a solvent, and the mixture was evenly ground in a mortar to obtain an electrode slurry, which was evenly scraped onto a copper foil, dried at 120°C in a vacuum oven for 24 hours, and the copper foil coated with the active material was punched into a disc with a diameter of 14 mm using a slicer to prepare an electrode sheet.
[0115] A CR2032 battery shell was selected, and a sodium sheet with a diameter of 14 mm was used as the negative electrode. A glass fiber separator, electrolyte, electrode sheet, gasket, spring sheet and positive electrode shell were placed in sequence. Finally, a battery packaging machine was used to assemble the half-cell. The energy storage carbon material obtained in Example 1 was used as the positive electrode to assemble a button-type sodium metal half-cell, and its coulomb efficiency was tested. The test diagram is shown in FIG. Fig. 9 shown.
[0116] Take two identical half-cells obtained in Example 1 and deposit the same capacity of metallic sodium at the same current density. Then disassemble the battery and take out the electrode sheet with pre-deposited sodium, use it as the electrode of the symmetrical battery, use CR2032 battery shell, and assemble it in the same way as the half-cell.
[0117] Take the half-cell of the electrode material obtained in Example 1, deposit a certain capacity of metallic sodium at a certain current density, disassemble and take out the electrode sheet as the negative electrode of the full battery, use commercial NVP (sodium vanadium phosphate) as the positive electrode, use CR2025 battery shell, and assemble the full battery according to the same procedure as the half-cell to test the rate performance and cycle performance. The test graph is as shown in the figure. Figure 11-12 shown.
[0118] In the full battery test, the voltage window is selected as 2.6-3.8V, and the rate test current density is selected as follows: 0.1C, 0.2C, 0.5C, 1C, 2C, 5C. The test results are shown in Table 4.
[0119] The electrodes made from the energy storage carbon materials of Examples 2-9 and the plant carbon materials of Comparative Example 1 were assembled with sodium sheets to form button-type sodium metal half-cells, and the test conditions were the same as above.
[0120] Comparative Example 2: The above-mentioned electrode coated with active material was replaced with a pure copper foil with a diameter of 14 mm, and a button-type sodium metal half-cell and a full cell were assembled according to the same experimental process for testing. The test conditions were the same as above.
[0121] All assembled batteries were left in open circuit at room temperature for 12 h before electrochemical testing.
[0122] Table 4 Test results of button-type sodium metal full battery
[0123]
[0124]
[0125] As can be seen from Table 4, the energy storage carbon materials prepared in Examples 1-9 have significant advantages in modifying the sodium metal negative electrode. At a current density of 0.1C, the specific capacity of the battery is higher than that at 100mAh g -1 Even when the current density increases to 5C, the specific capacity remains at 70 mAh g -1 As described above, good rate performance is shown, and the performance is significantly better than the pure plant carbon material of Comparative Example 1 and the pure copper foil of Comparative Example 2.
[0126] When the energy storage carbon materials prepared in Examples 1-9 are used as sodium metal battery modification materials, the -2 , 0.5mAh cm -2 The coulombic efficiency was tested in a button-type half-cell under the test conditions; 3 mAh cm was deposited on the electrode surface. -2 Sodium was used as the electrode of the symmetric battery to assemble a symmetric battery at 1 mA cm -2 , 0.5mAh cm -2 The cycle performance was tested under the test conditions of . The results are shown in Table 5.
[0127] Table 5 Sodium deposition peeling test results
[0128]
[0129]
[0130] It can be clearly seen from the above results that the energy storage carbon materials of Examples 1-9 have a -2 , 0.5mAh cm -2 Under the conditions of the above materials, the battery can be stably cycled for more than 1000 times with high Coulombic efficiency, and the voltage of the symmetrical battery assembled using the above materials can still maintain a relatively stable state after cycling for 500 hours. The battery performance is significantly better than the pure plant carbon material in Comparative Example 1 and the pure copper foil current collector in Comparative Example 2.
[0131] Test Example 3
[0132] The energy storage carbon materials prepared in Examples 1-9 and the plant carbon materials prepared in Comparative Example 1 were mixed with a conductive agent and a binder at a mass ratio of 8:1:1, wherein the conductive agent was acetylene black and the binder was PVDF (polyvinylidene fluoride). NMP (N-methylpyrrolidone) was used as a solvent, and the mixture was evenly ground in a mortar to obtain an electrode slurry, which was evenly scraped onto a copper foil, dried at 120°C in a vacuum oven for 24 hours, and the copper foil coated with the active material was punched into a disc with a diameter of 14 mm using a slicer to prepare an electrode sheet.
[0133] A CR2032 battery shell was selected, and a lithium sheet with a diameter of 14 mm was used as the negative electrode, followed by a glass fiber separator, electrolyte, electrode sheet, gasket, spring sheet, and positive electrode shell. Finally, a battery packaging machine was used to assemble the half-cell, and its coulombic efficiency was tested.
[0134] Take two identical half-cells obtained in Examples 1-9 and deposit metallic lithium of the same capacity at the same current density. Then disassemble the battery and take out the electrode sheet with pre-deposited lithium, use it as the electrode of the symmetrical battery, use CR2032 battery shell, and assemble it in the same way as the half-cell.
[0135] Take a half-cell of the electrode material obtained in Example 1-9, deposit a certain capacity of metallic lithium at a certain current density, disassemble and take out the electrode sheet as the negative electrode of the full battery, use commercial LFP (lithium iron phosphate) as the positive electrode, use a CR2025 battery shell, and assemble the full battery according to the same procedure as the half-cell to test the rate performance and cycle performance.
[0136] Comparative Examples 1 and 2 are pure plant carbon and pure copper foil, respectively. The test process is the same as that of the above Examples 1-9.
[0137] All assembled batteries were left in open circuit at room temperature for 12 h before electrochemical testing.
[0138] In the full battery test, the voltage window is selected as 2.8-4.2V, and the current density of the rate test is selected as follows: 0.5C, 1C, 2C, 5C, 10C, and 20C. The test results are shown in Table 6.
[0139] Table 6 Test results of button-type lithium metal full battery
[0140]
[0141]
[0142] It can be seen from Table 6 that when the energy storage carbon materials prepared in Examples 1-9 are used to modify the lithium metal negative electrode, the specific capacity of the full battery is maintained at 100 mAh g at a current density of 0.5 C. -1When the C is increased to 20C, the specific capacity is still 37-69 mAh g -1 The rate performance is significantly better than that of the pure plant carbon material in Comparative Example 1 and the pure copper foil in Comparative Example 2.
[0143] When the energy storage carbon materials prepared in Examples 1-9 are used as modified materials for lithium metal batteries, the -2 , 0.5mAh cm -2 The coulombic efficiency was tested in a button-type half-cell under the test conditions; 3 mAh cm was deposited on the electrode surface. -2 Lithium is used as an electrode in a symmetric battery. -2 , 0.5mAh cm -2 The cycle performance was tested under the test conditions of . The results are shown in Table 7.
[0144] Table 7 Lithium deposition stripping test results
[0145]
[0146]
[0147] From the above test results, it can be seen that at 1mA cm -2 , 0.5mAh cm -2 Under the test conditions, the coulombic efficiency can still be maintained above 97% after 500 cycles. The voltage of the assembled symmetrical battery can still remain stable after 300 hours of cycling. The long cycle performance is good, and the performance is significantly better than the pure plant carbon material in Comparative Example 1 and the pure copper foil in Comparative Example 2.
[0148] Test Example 4
[0149] The energy storage carbon materials prepared in Examples 1-9 and the plant carbon materials prepared in Comparative Example 1 were mixed with a conductive agent and a binder at a mass ratio of 8:1:1, wherein the conductive agent was acetylene black and the binder was PVDF (polyvinylidene fluoride). NMP (N-methylpyrrolidone) was used as a solvent, and the mixture was evenly ground in a mortar to obtain an electrode slurry, which was evenly scraped onto a copper foil, dried at 120°C in a vacuum oven for 24 hours, and the copper foil coated with the active material was punched into a disc with a diameter of 14 mm using a slicer to prepare an electrode sheet.
[0150] A CR2032 battery shell was selected, and a zinc sheet with a diameter of 10 mm was used as the negative electrode, followed by a glass fiber separator, electrolyte, electrode sheet, gasket, spring sheet, and positive electrode shell. Finally, a battery packaging machine was used to assemble the half-cell, and its coulombic efficiency was tested.
[0151] Take two identical half-cells obtained in Examples 1-9 and deposit the same capacity of metallic zinc at the same current density. Then disassemble the battery and take out the electrode sheet with pre-deposited zinc, which is used as the electrode of a symmetrical battery. Use a CR2032 battery shell and the assembly method is the same as that of the half-cell.
[0152] Take a half-cell of the electrode material obtained in Example 1-9, deposit a certain capacity of metallic zinc at a certain current density, disassemble and take out the electrode sheet as the negative electrode of the full cell, use commercial manganese dioxide as the positive electrode, use a CR2025 battery shell, and assemble the full cell according to the same procedure as the half-cell to test the rate performance and cycle performance.
[0153] Comparative Examples 1 and 2 are pure plant carbon and pure copper foil, respectively. The test process is the same as that of the above Examples 1-9.
[0154] All assembled batteries were left in open circuit at room temperature for 12 h before electrochemical testing.
[0155] In the full battery test, the voltage window is 1.0-3.8V, and the rate test current density is selected as follows: 0.2C, 0.5C, 1C, 2C, 5C. The test results are shown in Table 9.
[0156] Table 8 Button-type zinc metal full battery test results
[0157]
[0158]
[0159] It can be seen from Table 8 that when the energy storage carbon material prepared in Examples 1-9 is used to modify the zinc metal negative electrode, the specific capacity of the full battery is maintained at 120 mAh g at a current density of 5C. -1 As described above, the rate performance is significantly better than that of the pure plant carbon material in Comparative Example 1 and the pure copper foil in Comparative Example 2.
[0160] When the energy storage carbon materials prepared in Examples 1-9 are used as zinc metal battery modification materials, the -2 , 0.5mAh cm -2 The coulombic efficiency was tested in a button-type half-cell under the test conditions; 3 mAh cm was deposited on the electrode surface. -2 Zinc was used as an electrode in a symmetric cell to assemble a symmetric cell at 1 mA cm -2 , 0.5mAh cm -2 The cycle performance was tested under the test conditions of . The results are shown in Table 9.
[0161] Table 9 Zinc deposition peeling test results
[0162]
[0163]
[0164] From the above test results, it can be seen that at 1mA cm -2 , 0.5mAh cm -2 Under the test conditions, the coulombic efficiency can still be maintained above 90% after 500 cycles. The voltage of the assembled symmetrical battery can still remain stable after 300 hours of cycling. The long cycle performance is good, and the performance is significantly better than the pure plant carbon material in Comparative Example 1 and the pure copper foil in Comparative Example 2.
[0165] Therefore, compared with the currently reported electrode materials, the materials prepared by this method exhibit higher capacity and cycle stability.
[0166] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an energy storage carbon material, characterized in that: The method comprises: carbonizing biomass waste enriched with metal ions to obtain energy storage carbon material.
2. The method according to claim 1, wherein: The metal ion is selected from at least one of magnesium ion, calcium ion, chromium ion, manganese ion, iron ion, cobalt ion, nickel ion, copper ion, zinc ion, lead ion and cadmium ion.
3. The method according to claim 1 or 2, wherein: The carbonization is carried out under a protective atmosphere; Preferably, the protective atmosphere is an argon or nitrogen atmosphere; Preferably, the carbonization process comprises: heating to 100-300°C at a heating rate of 1-20°C / min and then keeping the temperature for 0.5-2h, then heating to 400-2000°C at the same heating rate and then keeping the temperature for 1-3h; Preferably, the carbonization process comprises: heating to 150°C at a heating rate of 2.5°C / min and then keeping the temperature for 30 minutes; then heating to 600°C at the same heating rate and then keeping the temperature for 1 hour.
4. The method according to any one of claims 1 to 3, wherein: The energy storage carbon material is a carbon material loaded with metal compound nanoparticles; Preferably, the metal compound is selected from at least one of magnesium oxide, magnesium sulfide, chromium oxide, chromium sulfide, manganese oxide, manganese sulfide, iron oxide, iron phosphide, iron sulfide, cobalt oxide, cobalt phosphide, cobalt sulfide, nickel oxide, nickel sulfide, nickel phosphide, nickel nitride, copper oxide, copper sulfide, copper phosphide, zinc oxide, zinc sulfide, zinc phosphide, cadmium oxide, cadmium sulfide, cadmium phosphide and metal compounds of the same family.
5. The method according to any one of claims 1 to 4, wherein: The biomass waste enriched with metal ions is obtained by the following method: the biomass waste is crushed, washed and dried, and added to wastewater containing metal ions for adsorption, and after the adsorption is completed, the biomass waste enriched with metal ions is obtained by centrifugal filtration.
6. The method according to any one of claims 1 to 5, wherein: The biomass waste contains S-glycoside, -SH, -NH2, PO, -OH or -COOH active functional groups; Preferably, the biomass waste is selected from at least one of rapeseed meal, bagasse and soybean meal.
7. The method according to any one of claims 1 to 6, wherein: The pH value of the metal ion-containing wastewater is 2-12, preferably 5-7; Preferably, the amount of biomass waste added is 0.1-100 g / L, preferably 1-20 g / L; Preferably, the adsorption time is 10-2000 min, preferably 500-1500 min, and more preferably 600 min.
8. The energy storage carbon material prepared according to the method according to any one of claims 1 to 7.
9. Use of the energy storage carbon material according to claim 8 in the preparation of secondary metal / ion batteries.
10. A secondary metal / ion battery, characterized in that: The battery uses the energy storage carbon material according to claim 8 as the negative electrode material.
Citation Information
Patent Citations
Method for preparing photocatalytic material from heavy metal ions in biological adsorption solution
CN104084221A
Method for preparing ultrafine powder material from valuable metal ions in biological adsorption solution
CN104057096A
Calcium modified biochar and preparation method and application thereof
CN105536704A
Method for treating industrial wastewater by utilizing biomass char and preparing graphite type porous carbon material
CN107814385A
Mg / Fe oxide modified biocarbon nano composite material and preparation method thereof
CN110801811A